2018
DOI: 10.1016/j.jhsa.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Long-Term Outcomes of Thumb Metacarpal Extension Osteotomy for Symptomatic Carpometacarpal Laxity and Early Basal Joint Arthritis

Abstract: Therapeutic IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…The authors reported satisfying clinical results for their patients [ 5 ]. Other studies also supported those first data, which have recently been extended to include long-term results [ 6 12 ].…”
Section: Introductionsupporting
confidence: 58%
“…The authors reported satisfying clinical results for their patients [ 5 ]. Other studies also supported those first data, which have recently been extended to include long-term results [ 6 12 ].…”
Section: Introductionsupporting
confidence: 58%
“…Thirty-two procedures in 7 males and 21 females were performed (mean age, 44.8 y). Overall, thumb metacarpal osteotomy provided some degree of pain relief and improvement of function [30].…”
Section: Discussionmentioning
confidence: 96%
“…Likewise [30] evaluated the survival and long-term outcomes of thumb metacarpal extension osteotomy for early CMC arthritis. Patients who underwent a thumb extension osteotomy between years 2000 and 2011 were identified.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 In a follow-up review of 13 patients, Chou et al 21 found that 77% of patients were satisfied or very satisfied at a mean follow-up of 9.9 years (range, 6–14 years). Bachoura et al 22 found that 7 of 32 operated thumbs (22%) required reoperation. Kaplan-Meier analysis of this series indicated a 70% probability that patients who had an extension osteotomy would not require additional CMC surgery for up to 14 years.…”
Section: Discussionmentioning
confidence: 98%